APPOINTMENT OF DIPLOMATIC HEAD AND STAFF ON IMIRGATION ATTACHES ABROAD - Jayadi Al Amien (Journal of Law and Border Protection, 2019)
As technology advances and it is easy for humans to move from one region to another, the flow of migration is getting faster and more intense. Of course, the role of the Asian government is very significant in terms of the entry and exit of people in the Territory of the Republic of Indonesia. In making it easier to carry out the Immigration function, it is necessary to establish Immigration representatives abroad, namely the Immigration Attaché and Immigration Technical Staff at the Representative Office of the Republic of Indonesia. Through normative research, the author aims to explain the duties and functions of the Immigration Attache and Immigration Technical Staff at the Indonesian Representative Office and their position as a representative of the Regional Office. The national interest of a country needs to have a relationship between countries in order to create social welfare. The researcher conveys the position of technical attaché and technical staff from an international legal point of view in order to place the duties and functions of the regional offices in the Representatives of the Republic of Indonesia Abroad.